2018
DOI: 10.1111/scs.12568
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of palliative care needs of patients/families living with cancer in a developing country

Abstract: This article focused on needs as expressed by patients and families and offers a useful guide to develop a model for integration of palliative care activities. The findings reveal that patients who are undergoing follow-up care and cancer treatment or investigation are clearly concerned about receiving information on a range of cancer issues. We therefore conclude that patients are able to deal with the disease more effectively when hospitals set up a palliative care team or unit to carry out proper assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 18 publications
(24 reference statements)
1
39
0
Order By: Relevance
“…Herrera and colleagues [34] remind us that PC provision should not be determined by the patient's geographical location, his/ her disease condition, or ability to pay, but on needs alone. Other studies [35,36] further support the contention that needs assessed deliberately among patients provide useful information to plan programmes and interventions that meet the explicit requirements of a local population. The ndings of this study are fundamental in developing PC services in Bhutan.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Herrera and colleagues [34] remind us that PC provision should not be determined by the patient's geographical location, his/ her disease condition, or ability to pay, but on needs alone. Other studies [35,36] further support the contention that needs assessed deliberately among patients provide useful information to plan programmes and interventions that meet the explicit requirements of a local population. The ndings of this study are fundamental in developing PC services in Bhutan.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have, however, found that cancer patients in the developed countries had higher unmet needs related to psychological and spiritual domains compared to patients in developing countries, whose main needs were pain medication, food and nancial support [74]. In developing countries, patients also had information needs about diagnosis, treatment options and side effects along with the need for psychological and spiritual support [35].…”
Section: Discussionmentioning
confidence: 99%
“…In order for nurses to provide early person‐centred palliative care, it is important that they have high levels of awareness and knowledge about the concept of person‐centred palliative care, as well as clarity of beliefs and values about person‐centred approaches to palliative care . In addition, an integrated approach to palliative care services needed .…”
Section: Discussionmentioning
confidence: 99%
“…In order for nurses to provide early person-centred palliative care, it is important that they have high levels of awareness and knowledge about the concept of person-centred palliative care, as well as clarity of beliefs and values about personcentred approaches to palliative care (8,9). In addition, an integrated approach to palliative care services needed (41). In studies to determine if nurses have sufficient knowledge of person-centred approaches to palliative care, it was shown that there is an increased need for further education of nurses in palliative care (17,18,42).…”
Section: Discussionmentioning
confidence: 99%
“…This study is limited in that it examined the patients' needs at the time of the study but does not indicate whether these needs changed as death approached. Ndiok 21 however, reported an important place of spiritual need among cancer patients followed in palliative care in Nigeria.…”
Section: Discussionmentioning
confidence: 99%